Ippaktuq Tasseok ("Harry") and wife in winter costume, Cape Fullerton, Hudson Bay, Canada - Comer, George (Creator); Lockwood, F.C. (Creator) (Ownership Statement: Mystic Seaport, 1905)
An Inuit man identified as "Harry" (Ippaktuq Tasseok) poses with his wife Patty in the deckhouse of the whaling schooner Era, Cape Fullerton, Hudson Bay, Canada, February 1, 1905. The couple are wearing winter dress. Lifestyle Infrastructure Title supplied by cataloger. Harry is referred to in the North as Comer's [Captain George Comer] "mate," and was the leader of a group of Iglulik Inuit known as the Aivilik or Aivillingmiut. These Inuit of the west coast region of Hudson Bay were closely associated with Comer and the American whalers for many years. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Slide prepared by F.C. Lockwood, Brooklyn, New York, from an original photograph by Captain George Comer. Slide was used by Comer to illustrate lectures about his Arctic and seafaring experiences.